(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The salt content of an agricultural field depends on the soil salinity and measuring its value precisely becomes essential. The dynamic changes of the factors are monitored using satellite data. This paper aims at estimating the value of soil pH based on the satellite data and the laboratory test results of pH values. Soil pH and salinity indices estimated from the satellite data has high correlation. A regression analysis is performed to explore the relationship between the salinity indices and the soil pH values over a study area. Salinity indices better represents the salt composition in the soil which is produced by reaction between the acidity and alkalinity as a chemical process. Based on the regression model the current soil pH value can be estimated with reference to the satellite data.